Verbalisasi Moderasi Beragama dalam Artikel Sarjana PTKIN Indonesia 2016-2020 - Abdul Malik; M. Anwar Hindi (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2021)
Abstract: The Indonesian Minister of Religion, Lukman Hakim Saifuddin, Fachrul Razi and Yaqul Cholil Qoumas, always gave directions to the Indonesian people to make religious moderation a shared commitment. One of the important elements of the implementation of religious moderation is carried out byscholar of Indonesian PTKIN in the form of reviewing journal articles. This article analyzes religious moderation in Indonesian PTKIN scholarships recorded in the form of journal articles from the first edition of 2016 to the second edition of 2020. To analyze these various articles, Verbalization will be adopted which was originally used to analyze the Qur'an for religious moderation. The Verbalization method, coined by Muhammad Alwi HS, has a strong epistemology, because it is based on the orallity of Qur'an which is the initial form as well as the identity of the Qur'an. Finally, this article concludes that PTKIN scholars are active in responding to the issue of religious moderation, which is carried out with various perspectives and scopes. What is more important is that almost all PTKIN scholars make efforts to verbalize religious moderation to the context or scope of their studies. This scholar is an important contribution of PTKIN scholars to efforts to produce patterns, guard, and develop religious moderation in Indonesia, especially since 2016-2020.